Detection and Molecular Mass Determination of an HIV Replication-Enhancing Female Genital Tract Factor Using a Blot Bioassay - Farhad B. Hashemi; Gregory T. Spear; Lawrence Madsen; Juergen Mollenhauer (BioTechniques)
We previously reported that cervicovaginal lavages (CVL) contain a factor that enhances the replication of human immunodefeciency virus (HIV) by increasing virus transcription in T cells and monocytoid cells. This factor was named the HIV-inducing factor (HIF). To determine the molecular mass of HIF, we adapted a blot technique that involves nonreducing SDS-PAGE of CVL samples and electrophoretic transfer onto nitrocellulose paper followed by incubation of paper slices with HIV-infected monocytoid U1 cells. The slices with HIF bioactivity were detected by increased HIV production and measured by an HIV core protein (p24) ELISA. We refer to this technique as the “BioBlot” assay. The BioBlot assay successfully detected bioactivity of HIF anchored onto nitrocellulose and determined that HIF has a molecular mass of about 14 kDa. Paper slices with HIF-negative CVL samples as well as nitrocellulose paper samples without CVL did not enhance HIV production. This finding suggested that SDS-PAGE and nitrocellulose binding do not functionally alter the bioactive domain(s) of HIF structure. In addition to the detection of HIF bioactivity anchored to nitrocellulose and HIF molecular mass determination, the BioBlot technique offers an alternative, rapid method for other applications. These include the study of receptor-ligand interactions of mucosal proteins, direct bioactivity testing and molecular mass determination of secretory substances.